A portrait of county sheriffs in the United States - Handberg, Roger (American journal of criminal justice, 1984)
A survey of county sheriffs in the United States was conducted in late Spring, 1983 (N=1526). The survey found county sheriffs to be basically a group of fairly professional law enforcement officials leavened by an influx of new amateurs. The sheriffs averaged over ten years experience in law enforcement along with an average of six years service as sheriff. Over half the sheriffs had prior service in the department they now head. In addition, they reported a wide variety of training experiences along with a number of assignments across the spectrum of law enforcement and corrections activities. Nearly twelve percent of the sheriffs report that they had relatives who had served as county sheriff before their tenure. These familial ties combined with the essentially local character of the office make county sheriffs a difficult institution to reform and individual sheriffs fairly independent of outsiders.